Report of the European Society of Cardiology Cardiovascular Round Table regulatory workshop update of the evaluation of new agents for the treatment of acute coronary syndrome: Executive summary: - Bueno, Héctor; Katus, Hugo (European heart journal - acute cardiovascular care, 2019)
Regulatory authorities interpret the results of randomized controlled trials according to published principles. The European Medicines Agency (EMA) is planning ...
First Published June 29, 2016
Gesehen am 28.01.2020